Organizational Learning as a Strategic Means for the Development of Human Resources and the Improvement of the Work Environment: A Case Study for Distinguished Businesses with the Best Workplace in Greece - Gkevorkian, Chrysoula; TSIBOUKLI, ANNA (Adult Education Critical Issues, 2025)
The main objective of modern organizations is to acquire a long-term competitive advantage, so that they may cope with the requirements of organizations' complex and unstable environment. In this context, several companies try to transform themselves into Learning Organizations. The aim of this paper is to reveal whether the awarded companies in Greece, in terms of working environment, provide learning opportunities to their employees within their working environment. The quantitative method was employed, and a reliable questionnaire was filled by 80 employees, who work for an awarded company as one of the best companies in Greece, by a certified international organization called "Great Place to Work", DLOQ-Dimensions of the Organization Learning Questionnaire with 55 items, was selected as a valid and reliable instrument, in order to evaluate the dimensions of organizational learning and organizational performance. The findings of the current research, indicate that the company under study, has the characteristics of a Learning Organization and that the adoption of the seven dimensions of the Learning Organization has a positive impact on organizational performance. According to the study results, the subject company, identifies the importance of developing a learning culture in order to increase its performance and due to this fact, it takes all actions required for the development and training of human resources, so that it may reach its objectives.